Species richness patterns and community structure of land snail communities along an urban-rural gradient in river floodplains - Čiliak, Marek; Čejka, Tomáš; Tej, Branislav; Oboňa, Jozef; Manko, Peter (Urban ecosystems, 2024)
Urbanisation is widely considered as having a large impact on most native species. However, the species response to urbanisation varies among taxonomic groups, and its generalisation might lead to contradictory or incorrect management decisions in urban planning. Land snails, as an understudied group in this sense, are good subjects to study the impact of urbanisation due to their low dispersal capabilities and mobility. The study aimed to determine how land snail diversity patterns and community structure are influenced by urbanisation through an urban-to-rural gradient. A total of 59 terrestrial gastropod species and more than 4600 individuals were recorded at 24 alluvial sites distributed along an urban-to-rural gradient in three Slovak cities (Bratislava, Zvolen and Prešov). Most species belonged to euryecious, hygrophilous and forest specialist ecological groups; seven species were non-native to Slovakia. The results clearly highlight the negative effect of densely built areas on land snail community structure, since the proportion of indigenous and specialist species decreased progressively towards urban sites. The highest mean number of species was found in suburban zones and the lowest in urban zones, suggesting that most species favour intermediate levels of urbanisation. Some species (e.g. Arion vulgaris ) were evenly distributed along the urbanisation gradient, supporting the importance of river floodplains as bio-corridors for the dispersal of gastropods.